Histopathological change of age-related hearing loss in female advance-aged CBA/CaJ mice - Yoshiaki Inuzuka; Kunio Mizutari; Takaomi Kurioka; Jun Suzuki; Yutaka Koizumi; Koji Araki; Akihiro Shiotani (PLoS ONE, 2025)
With the increase in the older population, the number of individuals with age-related hearing loss is also growing explosively. Therefore, there is an urgent need to identify the detailed pathology of age-related hearing loss and develop novel treatment strategies. In this study, we have investigated the audiological physiology and cochlear pathology of advanced-age CBA/CaJ mice, a strain that resists early pathological hearing loss. The subjects were naturally aged close to their lifespan limit (> two years) under normal in vivo conditions. We used 11 CBA/CaJ mice aged between 129 and 138 weeks to establish an aged group. To compare the electrophysiological function and histological changes, a young group was established using 12 young mice aged between 9 and 14 weeks. The loss of outer hair cells peaked at 11.3 kHz, and the greatest synapse loss was observed in the 5.6 kHz region, which was covered by the dominant frequency in the ambient sound. Furthermore, atrophy and microthrombus formation occurred in the stria vascularis, with endolymphatic hydrops observed in the cochlear apical turn. In the spiral ganglion and cochlear nerve, a reduction in the number of cells was accompanied by morphological changes indicative of cell aging. Increased levels of derivative-reactive oxygen metabolites, an oxidative stress marker, were observed in aged mice. These results indicate that age-related hearing loss involves a combined pathology of acoustic cochlear damage, which is potentially associated with chronic sound exposure and metabolic changes owing to mitochondrial dysfunction and oxidative stress accumulation. Accordingly, these two distinct etiologies must be addressed to prevent and treat age-related hearing loss.